2015
DOI: 10.1002/cpt.90
|View full text |Cite
|
Sign up to set email alerts
|

Improving evidence developed from population‐level experience with targeted agents

Abstract: Off-label drug use is common in oncology, due in part to significant unmet medical need, the rarity of many cancers, and the difficulty of conducting randomized controlled trials (RCTs) to support labeling of every drug in every disease setting. As new drugs are developed for use in tumors defined by genomic aberrations, it may be scientifically reasonable to expect that a targeted anti-cancer agent with efficacy in a biomarker-defined population within one tumor type may also have activity in another tumor ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When compared with old agents, off-label use of targeted therapies is probably more rational through tumoral genotyping but is faced with a limited clinical support, reimbursement challenges related to the very high pricing and the cost of genotyping or molecular profiling, when applicable. Beyond positive results published through anecdotal case reports, proposals have been made to gather clinical data relative to off-label use in the United States to get better evidence [28] . Furthermore, regarding enzyme inhibitors, their activity is generally characterized by a short duration of response due to the rapid development of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…When compared with old agents, off-label use of targeted therapies is probably more rational through tumoral genotyping but is faced with a limited clinical support, reimbursement challenges related to the very high pricing and the cost of genotyping or molecular profiling, when applicable. Beyond positive results published through anecdotal case reports, proposals have been made to gather clinical data relative to off-label use in the United States to get better evidence [28] . Furthermore, regarding enzyme inhibitors, their activity is generally characterized by a short duration of response due to the rapid development of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Others include institutional trials such as the IMPACT2 (NCT02152254) study being conducted at the University of Texas MD Anderson Cancer Center, which aims to expand on the early promise demonstrated by the earlier IMPACT (NCT00851032) study ( 70 ). Another exciting study that is expected to begin in late-2015, launched by the American Society for Clinical Oncology is the Targeted Agent and Profiling Utilization Registry (TAPUR) study, which aims to facilitate the matching of patients for which other therapeutic options are unavailable and whom harbor potentially actionable genomic alterations( 71,72 ). In this study patients alterations will be evaluated by a molecular tumor board, which will contain experts in genomically-guided medicine and the study will facilitate access to various targeted agents through collaborations with the pharmaceutical industry.…”
Section: Clinical Trials Utilizing Molecularly Guided Therapy Sementioning
confidence: 99%
“…With questions about meaningful clinical benefits and side effects and the high costs of many cancer therapies, a medical decision to pursue off‐label treatment may not have sufficient rationale in many scenarios. All these concerns heightened the reason to understand practice concerning off‐label drug use from the oncology practitioners’ perspective. A previous study in the United States reported significant variation in practice and attitudes among oncologists regarding such practice.…”
Section: Introductionmentioning
confidence: 99%